Perubahan Ruang Pada Bangunan Rumah Panjae Suku Dayak Iban Kalimantan Barat - Hafiid, Muammar Ardli; Antariksa, Antariksa; Ridjal, Abraham Mohammad (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
Long House (Rumah Panjae) Traditional Home Society of West Kalimantan Dayak Iban, long house or betang know in Dayak Iban language as Rumah Panjae. Long House (Rumah Panjae). Panjae Dayak Iban house is constructed of ironwood poles long, Rumah Panjae has its own meaning is backed by the confidence that exists in the customs and culture of the local community. Similarly, the change in house building Panjae is changing due to the needs of society. This study focuses on the problems of space changes in house building Dayak Iban language as Rumah Panjae West Kalimantan. This study aims to identify and analyze changes in the building space Dayak Iban House Panjae Utik River West Kalimantan. Conducting research using descriptive method, the survey directly into the field, the observed changes in the building space Panjae house. The study shows that changes that occur in the House chamber Panjae Dayak Iban influenced by the needs of today's society, such as the kitchen (Uji Bilik) and lounge (Kaki Lima) contained in the house being brought forward Panjae.Keyword: Rumah Panjae, Changes In Space